-7(5x+5)+4x=3x

Simple and best practice solution for -7(5x+5)+4x=3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(5x+5)+4x=3x equation:


Simplifying
-7(5x + 5) + 4x = 3x

Reorder the terms:
-7(5 + 5x) + 4x = 3x
(5 * -7 + 5x * -7) + 4x = 3x
(-35 + -35x) + 4x = 3x

Combine like terms: -35x + 4x = -31x
-35 + -31x = 3x

Solving
-35 + -31x = 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-35 + -31x + -3x = 3x + -3x

Combine like terms: -31x + -3x = -34x
-35 + -34x = 3x + -3x

Combine like terms: 3x + -3x = 0
-35 + -34x = 0

Add '35' to each side of the equation.
-35 + 35 + -34x = 0 + 35

Combine like terms: -35 + 35 = 0
0 + -34x = 0 + 35
-34x = 0 + 35

Combine like terms: 0 + 35 = 35
-34x = 35

Divide each side by '-34'.
x = -1.029411765

Simplifying
x = -1.029411765

See similar equations:

| 7y-x=9 | | .024a-8=.224a+2 | | 3(m-8)+-2=8 | | 6x+35=8x+15 | | 8t+2m=w-8 | | -22+t=36 | | -4(2t+2)=-32 | | -4(-6x+1)-3x=1 | | 25z-15=6z-14 | | .03x-3.9=.66 | | 7x+3x=5x+50 | | 8x+8-6x=-6 | | 25z-15=6z-24 | | 4=2(g-11)-2 | | (-7p)3= | | 2=7x-26 | | 15-g=6 | | -6+3(-8x+1)=15 | | 3(f-8)=-24 | | .04m=.08 | | 5t(10-3t)= | | 7/x-4=14/6 | | -5(4x-1)=-3x-6 | | 7-k=5 | | -7x-13+9x-19=-4 | | -1=2(j-8)+1 | | 10(s-6)=-146 | | 32-4x=18-6x | | 10y^2+90y=0 | | H=15t-4.9t^2+3 | | -2(8x+3)=3x | | 4x-x=7squared |

Equations solver categories